Analisis Probabilitas Kelongsoran Menggunakan Metode Monte Carlo Pada Highwall Pit SB-II BK-14 PT. Trubaindo Coal Mining, Site Melak, Kabupaten Kutai Barat, Kalimantan Timur - Panji Kurnia Wiradani; Bambang Heriyadi (Journals Mining Engineering : Bina Tambang, 2018)
Abstract. The wider and deeper the mine open in excavation, the greater the risks will arise or further improve uncertainty, on the factors that affect the stability of that open mining slope. This relates to the spatial variabelity in rocks laboratory testing, the handling of land cover, ground water level, and the weather. To predict the possibility of landslides, landslide probability analysis is applied by using the Monte Carlo method. The study was conducted on pit Highwall SB-II BK-14 especifically in cross section of A-A', B-B ',C-C’ D-D '. sequens mining Septermber 2017. The data obtained is the classification of rocks masses with RMR and GSI criteria, the slopes geometry, the ground water level, the physical and mechanical properties of rocks, and seismic hazard. Based on data processing, cross-section A-A has the landslide probability of 10.5% with FS (deterministic) 1.25 and Reliabilty index 1.12 (<3 means unreliable design) for cross-section B-B ', C-C’ and D-D ' has no value of landslide probability, but it does not mean there is no  possibility, as the mining activities progress the landslide probability will increase. Keywords:  Geotechnical, Probability analysis, Geological strength Indexs, Rock Mass Rating, Monte Carlo method